Auditory conflict and congruence in frontotemporal dementia. (September 2017) - Clark, Camilla N.; Nicholas, Jennifer M.; Agustus, Jennifer L.; Hardy, Christopher J.D.; Russell, Lucy L.; Brotherhood, Emilie V.; Dick, Katrina M.; Marshall, Charles R.; Mummery, Catherine J.; Rohrer, Jonathan D.; Warren, Jason D.
Abstract: Impaired analysis of signal conflict and congruence may contribute to diverse socio-emotional symptoms in frontotemporal dementias, however the underlying mechanisms have not been defined. Here we addressed this issue in patients with behavioural variant frontotemporal dementia (bvFTD; n = 19) and semantic dementia (SD; n = 10) relative to healthy older individuals (n = 20). We created auditory scenes in which semantic and emotional congruity of constituent sounds were independently probed; associated tasks controlled for auditory perceptual similarity, scene parsing and semantic competence. Neuroanatomical correlates of auditory congruity processing were assessed using voxel-based morphometry. Relative to healthy controls, both the bvFTD and SD groups had impaired semantic and emotional congruity processing (after taking auditory control task performance into account) and reduced affective integration of sounds into scenes. Grey matter correlates of auditory semantic congruity processing were identified in distributed regions encompassing prefrontal, parieto-temporal and insular areas and correlates of auditory emotional congruity in partly overlapping temporal, insular and striatal regions. Our findings suggest that decoding of auditory signal relatedness may probe a generic cognitive mechanism and neural architecture underpinning frontotemporal dementia syndromes. Highlights: Socioemotional changes in frontotemporal dementia may reflect altered signal decoding. To address this, we varied semantic and emotional signal relatedness in sound scenes. Frontotemporal dementia patients had impaired semantic and emotional scene decoding. These deficits correlated with atrophy of distributed cortico-subcortical regions. Signal processing approaches may help deconstruct complex dementia phenotypes.